(untitled) (European Journal of Pure and Applied Mathematics, 2025)
This paper introduces new classes of continuous multifunctions defined between an ideal topological space and a bitopological space, called upper almost τ^α(σ_1,σ_2)-continuous multifunctions and lower almost τ^α(σ_1,σ_2)-continuous multifunctions. Furthermore, several characterizations and some properties concerning upper almost τ^α(σ_1,σ_2)-continuous multifunctions and lower almost τ^α(σ_1,σ_2)-continuous multifunctions are investigated.